Identification of potential pathogenic mutations in Chinese children with first branchial cleft anomalies detected by whole‐exome sequencing. Issue 3 (23rd June 2021) - Yang, Yeran; Liu, Wei; Jin, Yaqiong; Chen, Min; Lu, Jie; Yu, Yongbo; Ren, Huimin; Han, Shujing; Chu, Ping; Guo, Yongli; Zhang, Jie; Ni, Xin
ABSTRACT: Importance: First branchial cleft anomalies (FBCAs) are rare congenital malformations, accounting for < 8% of all branchial cleft anomalies. However, little is currently known about the cause of FBCAs at the molecular level. Objective: To identify genomic alterations related to the genetic etiology of FBCAs in Chinese children. Methods: We performed whole‐exome sequencing of samples from 10 pediatric patients with FBCAs. Data analysis was carried out using the Burrow‐Wheeler Alignment software package, and the dbSNP database for comparisons. Rare variants were further validated by Sanger sequencing. Insertion/deletions (indels) were examined using the Genome Analysis Toolkit. Results: We identified 14 non‐synonymous mutations in seven potential FBCA‐susceptibility genes ( TRAPPC12, NRP2, NPNT, SH3RF2, RHPN1, TENM4, and ARMCX4 ). We also detected 133 shared small indels in 125 genes. Gene Ontology analysis indicated that most of the identified genes played critical roles in development and differentiation pathways involved in regulating organ development. Interpretation: We characterized the mutational landscape in pathways involved in development and differentiation in Chinese children with FBCA. The results identified potential pathogenic genes and mutations related to FBCA, and provide molecular‐level support for the branchial theory of FBCA pathogenesis. Abstract : Workflow for the identification of potential pathogenic mutations in the first branchial cleft anomalies in Chinese children by whole exome sequencing.